Development and Application of a PCR-Targeted Gene Disruption Method for Studying CelR Function in Thermobifida fusca - Deng, Yu (American Society for Microbiology (ASM), 2010)
Thermobifida fusca is a high-G+C-content, thermophilic, Gram-positive soil actinobacterium with high cellulolytic activity. In T. fusca, CelR is thought to act as the primary regulator of cellulase gene expression by binding to a 14-bp inverted repeat [5′-(T)GGGAGCGCTCCC(A)] that is upstream of many known cellulase genes. Previously, the ability to study the roles and regulation of cellulase genes in T. fusca has been limited largely by a lack of established genetic engineering methods for T. fusca. In this study, we developed an efficient procedure for creating precise chromosomal gene disruptions and demonstrated this procedure by generating a celR deletion strain. The celR deletion strain was then characterized using measurements for growth behavior, cellulase activity, and gene expression. The celR deletion strain of T. fusca exhibited a severely crippled growth phenotype with a prolonged lag phase and decreased cell yields for growth on both glucose and cellobiose. While the maximum endoglucanase activity and cellulase activity were not significantly changed, the endoglucanase activity and cellulase activity per cell were highly elevated. Measurements of mRNA transcript levels in both the celR deletion strain and the wild-type strain indicated that the CelR protein potentially acts as a repressor for some genes and as an activator for other genes. Overall, we established and demonstrated a method for manipulating chromosomal DNA in T. fusca that can be used to study the cellulolytic capabilities of this organism. Components of this method may be useful in developing genetic engineering methods for other currently intractable organisms.